Phytosociology of Trees in Siranggas Wildlife Sanctuary Area, North Sumatra, Indonesia - Tarigan, Ahmad Fikry; Siregar, Etti Sartina (Journal of Tropical Biodiversity and Biotechnology, 2025)
The lower mountainous region’s Siranggas Wildlife Sanctuary is a conservation area with a variety of tree species, however it is susceptible to exploitation-related harm. Despite the area’s ecological advantages, little is known about the diversity of tree species and their associations. Therefore, the purpose of this study was to ascertain the Siranggas Wildlife Sanctuary Area’s tree species diversity and associations. Using the purposive sampling approach, the study was carried out from March to April 2022. Five plots, each measuring 30 by 60 meters, were set up at various heights. The Importance Value Index (IVI) and the Shannon-Wiener Diversity Index (H’) were used to examine the vegetation data. Associations between tree species were identified by considering two species with the highest IVI in the observation plot. The results showed that there were 119 tree species, 38 families, and 79 genera in the Siranggas Wildlife Sanctuary Area. The diversity index across the plot was relatively high with an H’ value > 3. Trees with a height of 10 to 15 meters were the prevalent canopy height profile in the plot, while the dominant trunk diameter across the whole plot was 10 to 20 cm. The association that occurred in the study area was the Schima wallichii – Syzygium cerasiforme based on two of the greatest IVI and their distribution throughout all plots from varying altitudes. Future forest management and restoration initiatives in the Siranggas Wildlife Sanctuary area can benefit from the presence of both of these species.